Links between work experiences and organizational commitment during the first year of employment : a longitudinal analysis - Meyer, John P. [Verfasser]; Allen, Natalie J. [Verfasser] (My University, 1988)
"In this study, the Organizational Commitment Questionnaire and self-report measures of work experiences were completed by newly hired university graduates 1,6 and 11 months after starting employment. The time-lagged influence of work experiences on commitment, and of commitment on work experiences, was examined using struktural regression analyses. The results revealed effects of work experiences in the first month of employment on commitment measured after 6 and 11 months. The strongest and most consistent effects were obtained for confirmation of pre-entry expectations and the opportunity for self-expression. Some, albeit weaker, evidence was also provided for time-lagged effects of commitment on perceived work experiences, particularly in the 6-11 month lag. Implications for theory and research concerning the development of commitment are discussed." (author's abstract) ((en)) In der Studie wird der Zusammenhang zwischen Arbeitserfahrungen und Unternehmensbindung von Berufsanfängern mit Hochschulabschluss in den ersten Monanten nach der Einstellung überprüft. Die Untersuchung basiert auf einer Längsschnittbefragung von 97 Absolventen der University of Western Ontario. Die Ergebnisse zeigen, dass die Erfahrungen, die die Arbeitnehmer kurz nach dem Eintritt in die Organisation machen, instrumentell ihre Identifikation mit dem Unternehmen prägen. Grossen Einfluss auf die Bindung an das Unternehmen kommt der Stärke der Einstellungen vor Antritt der Stelle zu. Überraschend zeigte sich, dass auch der Faktor Selbstverwirklichung die Einstellungen der Berufsanfänger entscheidend beeinflusst. (IAB)
Arbeitserfahrung und Unternehmensbindung im ersten Jahr der Beschäftigung
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; P 2 Zielgruppen nach Bildungsstatus; G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.4.4 Biografiegestaltung; P 2.1.5 Fachhochschul- und Hochschulreife; Betriebstreue; Berufsanfänger; Arbeitszufriedenheit; Berufserfahrung; Arbeitssituation; Hochschule; Absolvent; Quantitative Angaben